Complexity and benefit take-up: Empirical evidence from the Finnish homecare allowance - Tomer Blumkin; Tuomas Kosonen; Kaisa Kotakorpi (Aboa Centre for Economics (ACE), 2018)
We analyse to what extent the complexity of benefit rules affects take-up in a setting where the effects of complexity can be separated from other potential causes of non-take-up. The benefit we study is extensively used by individuals from all socioeconomic groups, namely the municipal supplement to the child homecare allowance in Finland. We use individual-level data on mothers of young children together with municipal-level data on the application rules for the benefit. Variation in the supplement rules between municipalities and over time is used to estimate the causal effect of complexity on take-up. We find in a differences-in-differences setting that complexity has a very large effect on take-up. Complex application procedures cause individuals to forego a benefit of approximately 200 exteuro per month, potentially for 2 years.
Keywords: I38; H31; H53; 330; benefit take-up; complexity; childcare